Tube-Test of Antibiofilm Activity of Yellow Root Extract (Fibraurea tinctoria Lour.) Against Bacteria Causing Impetigo - Lia Yulia Budiarti; Arisanty Dewi; Yafi Fahmi; Agung Biworo (Berkala Kedokteran, 2025)
Impetigo is a contagious superficial bacterial skin infection that commonly occurs in children. The main causative agents are Staphylococcus aureus (S. aureus) and Streptococcus pyogenes (S. pyogenes). Both types of bacteria are capable of forming biofilms, making them resistant to antimicrobial agents. Antimicrobial agents that affect the survival of biofilm-forming bacteria are not only derived from synthetic drugs but also from phytochemical compounds. The antibiofilm effect can be assessed through a tube-test. Fibraurea tinctoria Lour (F. tinctoria), known as yellow root, contains various antibacterial compounds and has the potential as an antibiofilm agent. This experimental study aims to evaluate the ability of F. tinctoria root extract as an antibiofilm against S. aureus and S. pyogenes as the causative agents of impetigo in vitro. The study design used a post-test only with control group design with a tube-test method. The antibiofilm effect of F. tinctoria root extract at concentrations of 3.125%-50% and a 0.5% ampicillin control were tested on standard ATCC isolates of S. aureus and S. pyogenes. The observed parameters were the Minimum Biofilm Inhibitory Concentration (MBIC) and Mean Gray Value (MGV). The result showed F. tinctoria extract inhibited the biofilm formation of the tested bacteria. The antibiofilm activity was significantly influenced by extract concentration (P > 0.05). The MBIC value of the extract was found at a concentration of 12.5%, with MGV against S. aureus ranging from 130.303-157.3833 and 131.9767-160.1833 against S. pyogenes. In conclusion, F. tinctoria root extract demonstrates antibiofilm effects in vitro against the two tested bacteria that cause impetigo.